Nitrogen / phosphorus co-doped hard carbon and preparation method and application thereof

By using yeast as the carbon source, the hard carbon preparation process is simplified and uniform co-doping of nitrogen/phosphorus elements is achieved, which solves the problem of poor electrochemical performance of existing hard carbons. The prepared nitrogen/phosphorus co-doped hard carbon Has excellent sodium-ion battery performance.

CN119330333AActive Publication Date: 2025-01-21SOUTHWEST JIAOTONG UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411334326.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-21
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The existing hard carbon preparation process is complex and has poor electrochemical performance when used as an electrode material, especially in sodium ion batteries, low first-week Coulomb efficiency, poor cycle stability, and large polarization under high current density.

Method used

Using microbial yeast that is naturally rich in nitrogen/phosphorus as the carbon source, nitrogen/phosphorus co-doped hard carbon is prepared through heat treatment and high-temperature calcination of the yeast culture solution, which simplifies the preparation process and achieves uniform nitrogen/phosphorus elements. Co-mixed.

Benefits of technology

The prepared nitrogen/phosphorus co-doped hard carbon has a nanopore structure, which provides a large number of sodium storage active sites, improves the migration ability and fast charging ability of sodium ions, and also improves the stability and cycle performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330333A_ABST
    Figure CN119330333A_ABST
Patent Text Reader

Abstract

The invention discloses nitrogen / phosphorus co-doped hard carbon as well as a preparation method and application thereof, and belongs to the technical field of battery materials. Yeast is used as a raw material, the nitrogen / phosphorus co-doped biomass-based hard carbon is prepared through culture multiplication and high-temperature calcination processes, and the material is used as a negative electrode to be applied to a sodium ion battery. Compared with a traditional method for preparing hard carbon based on biomass, the method has the advantages that the biomass can be used as a carbon source, and nitrogen / phosphorus co-doped hard carbon is formed in the preparation process of the hard carbon by utilizing the nitrogen and phosphorus containing characteristics of microorganisms. The electron-rich heteroatoms enable the prepared hard carbon to have more sodium ion active sites, the electron conductivity can be improved, the electrochemical capacity of the hard carbon can be improved, and the hard carbon shows excellent electrochemical performance when applied to the negative electrode of the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a nitrogen / phosphorus co-doped hard carbon and a preparation method and application thereof. Background Art

[0002] Sodium ion batteries (SIBs) play an important role in the future energy storage field due to their advantages such as abundant sodium reserves and low price. The development of SIBs involves many national priority development areas such as "electrochemical energy beyond traditional systems, low-carbon energy power systems and theory and technology of efficient and high-quality utilization of electric energy", and is one of the major development areas in my country.

[0003] Hard carbon has become the most promising negative electrode material for the commercialization of SIBs due to its advantages such as wide raw material sources, multiple active sites, high sodium storage capacity, and high safety. However, the practical application of hard carbon has been hindered by problems such as low first-week coulombic efficiency, poor cycle stability, and large polarization at high current density. To this end, the introduction of heteroatom (nitrogen, phosphorus, etc.) doping to expand the interlayer spacing of graphite crystallites in hard carbon and increase sodium affinity, thereby improving the electrochemical performance of sodium-ion batteries, has attracted widespread attention from scientific researchers. However, the addition of nitrogen and phosphorus sources during the synthesis of hard carbon can easily cause uneven distribution of nitrogen / phosphorus or make it difficult to introduce, and complicate the preparation steps of hard carbon. In addition, when biomass is used as a carbon source, it is difficult to uniformly and effectively add nitrogen and phosphorus sources during the preparation of hard carbon. Therefore, exploring a natural nitrogen / phosphorus-rich biomass as a carbon source to prepare hard carbon is conducive to achieving uniform co-doping of nitrogen / phosphorus, enhancing the electrochemical performance of sodium-ion batteries, and promoting the development of new hard carbon carbon sources and their commercial application. Summary of the invention

[0004] In view of the above-mentioned prior art, the present invention provides a nitrogen / phosphorus co-doped hard carbon and a preparation method and application thereof, so as to solve the technical problems of the complex preparation process of the prior hard carbon and the poor electrochemical performance when used as an electrode material.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is to provide a method for preparing nitrogen / phosphorus co-doped hard carbon, comprising the following steps:

[0006] S1: Cultivating yeast with glucose solution to obtain yeast culture solution;

[0007] S2: heat-treating the yeast culture solution, and then washing and drying it to obtain a precursor;

[0008] S3: In an inert atmosphere, heat the precursor to 900-1500°C, keep it at this temperature for 2 hours, then cool it to 500°C at a cooling rate of 4°C / min, and then cool it to room temperature in the furnace.

[0009] Based on the above technical solution, the present invention can also be improved as follows.

[0010] Furthermore, the yeast culture method in S1 is: 3.5 g of yeast is inoculated into 80 mL of 0.2 M glucose solution and cultured at room temperature for 24 h.

[0011] Furthermore, the heat treatment method in S2 is to put the yeast culture solution into a hydrothermal kettle and keep it at 105°C for 1 hour.

[0012] Furthermore, the cleaning method in S2 is to wash twice with deionized water and anhydrous ethanol respectively.

[0013] Furthermore, in S2, the drying temperature is 60° C. and the drying time is 24 h.

[0014] Furthermore, the inert atmosphere is an argon atmosphere.

[0015] Furthermore, the heating rate in S3 is 3°C / min.

[0016] The invention also discloses a hard carbon rich in nitrogen / phosphorus prepared by the preparation method.

[0017] The present invention also discloses the application of the nitrogen / phosphorus co-doped hard carbon in the preparation of a sodium ion battery. Specifically, the nitrogen / phosphorus co-doped hard carbon is used as the negative electrode material of the sodium ion battery.

[0018] The beneficial effects of the present invention are:

[0019] 1. The present invention utilizes microbial fungi (yeast) naturally rich in nitrogen / phosphorus to prepare nitrogen / phosphorus co-doped hard carbon. No nitrogen source and phosphorus source need to be added during the preparation process, which not only simplifies the preparation process but also avoids the problem of uneven nitrogen / phosphorus distribution.

[0020] 2. By adopting the preparation process of the present invention, the water-containing components in the precursor are removed at high temperature, and the prepared nitrogen / phosphorus co-doped hard carbon contains a nanopore structure, which can provide a large number of sodium storage active sites, which is conducive to the embedding and removal of sodium ions during the charging and discharging process. In addition, the prepared nitrogen / phosphorus co-doped hard carbon, due to the electron-rich structure of nitrogen / phosphorus elements, is conducive to the migration of sodium ions during the charging and discharging process, which can enhance the fast charging ability of the hard carbon negative electrode; at the same time, the present invention uses natural nitrogen / phosphorus-rich substances to prepare hard carbon, and nitrogen / phosphorus elements can be evenly distributed in the hard carbon, and the prepared hard carbon material has stable long-cycle performance.

[0021] 3. The present invention utilizes biological fungi naturally rich in nitrogen / phosphorus elements to prepare nitrogen / phosphorus co-doped hard carbon, which improves the electronic conductivity of the hard carbon material and provides more sodium storage active sites, thereby improving the discharge specific capacity of the hard carbon material. The biomass used in the present invention can not only be used as a carbon source to prepare hard carbon, but also provide nitrogen and phosphorus sources. Therefore, in the prepared hard carbon material, nitrogen and / or phosphorus elements can be evenly dispersed on the surface and inside of the hard carbon material. Such an electron-rich structure is conducive to the migration of sodium ions during the charge and discharge process, and helps to improve the high-rate performance of sodium ion batteries. The hard carbon prepared by the present invention using biological bacteria contains a nanopore structure, which is conducive to the storage of sodium ions and improves the reversible capacity of the hard carbon. The nitrogen / phosphorus co-doped hard carbon prepared by the present invention has good rate performance and cycle stability. At 0.1C (1C = 300mAh g -1 ) can reach 309mAh g -1 , and the capacity retention rate is still 88.9% after 1000 cycles at 1C.

[0022] 4. The preparation process of the present invention is simple to operate and can stimulate the development and application of low-cost biomass containing electron-rich elements such as natural nitrogen and phosphorus in hard carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is the X-ray crystal diffraction pattern of nitrogen / phosphorus co-doped hard carbon obtained in Examples 1 to 4;

[0024] Figure 2 The Raman spectra of nitrogen / phosphorus co-doped hard carbon obtained in Examples 1 to 4;

[0025] Figure 3 This is the X-ray electron spectrum of the nitrogen / phosphorus co-doped hard carbon obtained in Example 3;

[0026] Figure 4 This is a high-resolution transmission electron micrograph of the nitrogen / phosphorus co-doped hard carbon obtained in Examples 1 to 4. DETAILED DESCRIPTION

[0027] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0028] Example 1

[0029] A nitrogen / phosphorus co-doped hard carbon is prepared by the following steps:

[0030] S1: Inoculate 3.5 g of yeast into 80 mL of 0.2 M glucose solution and culture at room temperature for 24 h to obtain yeast culture solution;

[0031] S2: Place the yeast culture solution in a hydrothermal autoclave and keep it at 105°C for 1 hour; then cool the obtained product and wash it twice with deionized water and ethanol respectively by centrifugation, then transfer the centrifuged product to a forced air drying oven and bake it at 60°C for 24 hours to obtain a precursor;

[0032] S3: The precursor is transferred to a graphite porcelain boat, and the graphite porcelain boat containing the precursor is transferred to a tubular furnace. The temperature is increased to 900°C at a heating rate of 3°C / min under an argon atmosphere, and kept at this temperature for 2 hours to form a disordered graphite microcrystalline structure; the temperature is then decreased to 500°C at a cooling rate of 4°C / min, and then cooled to room temperature with the furnace to obtain nitrogen / phosphorus co-doped hard carbon.

[0033] Example 2

[0034] A nitrogen / phosphorus co-doped hard carbon is prepared by the following steps:

[0035] S1: Inoculate 3.5 g of yeast into 80 mL of 0.2 M glucose solution and culture at room temperature for 24 h to obtain yeast culture solution;

[0036] S2: Place the yeast culture solution in a hydrothermal autoclave and keep it at 105°C for 1 hour; then cool the obtained product and wash it twice with deionized water and ethanol respectively by centrifugation, then transfer the centrifuged product to a forced air drying oven and bake it at 60°C for 24 hours to obtain a precursor;

[0037] S3: The precursor is transferred to a graphite porcelain boat, and the graphite porcelain boat containing the precursor is transferred to a tubular furnace. The temperature is increased to 1100°C at a heating rate of 3°C / min under an argon atmosphere, and kept at this temperature for 2 hours to form a disordered graphite microcrystalline structure; the temperature is then decreased to 500°C at a cooling rate of 4°C / min, and then cooled to room temperature with the furnace to obtain nitrogen / phosphorus co-doped hard carbon.

[0038] Example 3

[0039] A nitrogen / phosphorus co-doped hard carbon is prepared by the following steps:

[0040] S1: Inoculate 3.5 g of yeast into 80 mL of 0.2 M glucose solution and culture at room temperature for 24 h to obtain yeast culture solution;

[0041] S2: Place the yeast culture solution in a hydrothermal autoclave and keep it at 105°C for 1 hour; then cool the obtained product and wash it twice with deionized water and ethanol respectively by centrifugation, then transfer the centrifuged product to a forced air drying oven and bake it at 60°C for 24 hours to obtain a precursor;

[0042] S3: The precursor is transferred to a graphite porcelain boat, and the graphite porcelain boat containing the precursor is transferred to a tubular furnace. The temperature is increased to 1300°C at a heating rate of 3°C / min under an argon atmosphere, and kept at this temperature for 2 hours to form a disordered graphite microcrystalline structure; the temperature is then decreased to 500°C at a cooling rate of 4°C / min, and then cooled to room temperature with the furnace to obtain nitrogen / phosphorus co-doped hard carbon.

[0043] Example 4

[0044] A nitrogen / phosphorus co-doped hard carbon is prepared by the following steps:

[0045] S1: Inoculate 3.5 g of yeast into 80 mL of 0.2 M glucose solution and culture at room temperature for 24 h to obtain yeast culture solution;

[0046] S2: Place the yeast culture solution in a hydrothermal autoclave and keep it at 105°C for 1 hour; then cool the obtained product and wash it twice with deionized water and ethanol respectively by centrifugation, then transfer the centrifuged product to a forced air drying oven and bake it at 60°C for 24 hours to obtain a precursor;

[0047] S3: The precursor is transferred to a graphite porcelain boat, and the graphite porcelain boat containing the precursor is transferred to a tubular furnace. The temperature is increased to 1500°C at a heating rate of 3°C / min under an argon atmosphere, and kept at this temperature for 2 hours to form a disordered graphite microcrystalline structure; the temperature is then decreased to 500°C at a cooling rate of 4°C / min, and then cooled to room temperature with the furnace to obtain nitrogen / phosphorus co-doped hard carbon.

[0048] Experimental example

[0049] 1. Structural analysis

[0050] The nitrogen / phosphorus co-doped hard carbon prepared in Examples 1 to 4 was tested by X-ray electron diffraction. The results are as follows: Figure 1 As shown in the figure, it can be seen that the nitrogen / phosphorus co-doped hard carbon prepared in Examples 1 to 4 has two characteristic broad peaks of hard carbon (002) and (100). In addition, with the increase of calcination temperature, the (002) peak gradually shifts to a high angle, indicating that the degree of graphitization in the hard carbon increases.

[0051] Raman tests were performed on the nitrogen / phosphorus co-doped hard carbons prepared in Examples 1 to 4 to characterize the degree of defects in the hard carbons. The results are as follows: Figure 2 As shown in the figure, it can be seen that the defect peak area (A D ) and graphite peak area (A G ) ratios are 1.89, 1.77, 1.65, and 1.50, respectively, indicating that higher temperatures will remove defects on the hard carbon surface, such as functional groups.

[0052] The nitrogen / phosphorus co-doped hard carbon prepared in Example 3 was tested by X-ray photoelectron spectroscopy (XPS). Figure 3 As shown in the figure, it can be seen that the prepared hard carbon contains nitrogen and phosphorus elements, which confirms that the hard carbon prepared by yeast is co-doped with nitrogen and phosphorus.

[0053] The morphology of the nitrogen / phosphorus co-doped hard carbon prepared in Examples 1 to 4 was observed by high resolution transmission electron microscopy (HRTEM). Figure 4 As shown in the figure, it can be seen that the hard carbon prepared by the process of the present invention has the typical characteristics of hard carbon, "long-range disorder, short-range order", which is conducive to the deintercalation of sodium ions. In addition, the presence of nanopores can be observed in HRTEM, which is conducive to the storage of sodium ions, thereby improving the reversible specific capacity of the hard carbon.

[0054] 2. Electrochemical performance test

[0055] 1. Preparation of button cells

[0056] The nitrogen / phosphorus co-doped hard carbon prepared in Examples 1 to 4 was made into CR2032 button cells for electrochemical performance testing. The specific steps are: the prepared hard carbon is configured into a slurry according to a mass ratio of hard carbon: acetylene black: binder (PVDF) = 8:1:1, and N,N-dimethylpyrrolidone (NMP) is used as a solvent, and coated on a conductive copper foil to obtain an electrode. After the prepared electrode is dried in a blast oven at 60°C for 6 hours, it is transferred to a vacuum oven and continued to be dried at 100°C for 12 hours. The dried electrode is cut into small discs with a diameter of 10 mm using a tablet punching machine, and the active material loading is approximately 1.0 to 1.5 mg / cm -2 In a glove box (oxygen content less than 0.01ppm, water content less than 0.01ppm), the obtained small disc was used as the negative electrode, the sodium sheet was used as the positive electrode, and was packaged into a 2032 button half-cell in the assembly order with a glass fiber separator, an electrolyte (1M NaPF6 in Diglyme) gasket, a spring, and positive and negative electrode shells.

[0057] 2. Test of electrochemical performance

[0058] The assembled button half-cell was charged and discharged on the Xinwei test channel. The voltage range of the cycle test was 0.01~2.0V, and 1C was defined as 300mAg -1 The test results are summarized in Table 1.

[0059] Table 1 Summary of electrochemical performance of hard carbon prepared in Examples 1-4

[0060]

[0061] As can be seen from Table 1, the nitrogen / phosphorus co-doped hard carbon obtained by the preparation method provided by the present invention exhibits higher reversible capacity and better cycle stability. Especially Example 3, which still has a retention rate of 88.9% after 1000 cycles at 1C. Due to the nitrogen / phosphorus doping and the degree of graphitization, Examples 3 and 4 exhibit higher reversible capacity at high current density (5C). The reason why Examples 1 and 2 have lower reversible capacity at 5C is that the calcination temperature is low, the interlayer spacing of graphite crystallites in the hard carbon is larger, and the degree of graphitization is low, which is not conducive to the storage of sodium ions.

[0062] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments and drawings, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A method for preparing nitrogen / phosphorus co-doped hard carbon, characterized in that: The following steps are involved: S1: Cultivating yeast with glucose solution to obtain yeast culture solution; S2: heat-treating the yeast culture solution, and then washing and drying it to obtain a precursor; S3: In an inert atmosphere, heat the precursor to 900-1500°C, keep it at this temperature for 2 hours, then cool it to 500°C at a cooling rate of 4°C / min, and then cool it to room temperature in the furnace.

2. The preparation method according to claim 1, characterized in that: The yeast culture method in S1 is as follows: 3.5 g of yeast was inoculated into 80 mL of 0.2 M glucose solution and cultured at room temperature for 24 h.

3. The preparation method according to claim 1, characterized in that: The heat treatment method in S2 is to put the yeast culture solution into a hydrothermal kettle and keep it at 105°C for 1 hour.

4. The preparation method according to claim 1, characterized in that: The cleaning method in S2 is to wash twice with deionized water and anhydrous ethanol respectively.

5. The preparation method according to claim 1, characterized in that: The drying temperature in S2 is 60°C and the drying time is 24h.

6. The preparation method according to claim 1, characterized in that: The inert atmosphere is an argon atmosphere.

7. The preparation method according to claim 1, characterized in that: The heating rate in S3 is 3°C / min.

8. Nitrogen / phosphorus co-doped hard carbon obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the nitrogen / phosphorus co-doped hard carbon according to claim 8 in the preparation of sodium ion batteries.

10. The use according to claim 9, characterized in that: The nitrogen / phosphorus co-doped hard carbon is used as the negative electrode material of the sodium ion battery.

Citation Information

Patent Citations

  • Preparation method for MoS2@C composite electrode material using strain charcoal as carbon source

    CN109309225A

  • Biochar material loaded with magnesium and phosphate ions and application of material in denitrification of leather waste water

    CN109574247A

  • Hollow biological carbon sphere-based nickel sulfide nanorod supercapacitor and preparation method

    CN110060873A

  • Biomass-derived carbon material with high specific area and high doped nitrogen content, and preparation method and application thereof

    CN110690465A

  • Nitrogen and phosphorus co-doped carbon-based CoFe alloy nano material as well as preparation method and application thereof

    CN112264068A